Methods of exploring emotions - Flam, Helena; Kleres, Jochen (London : Routledge, 2015)
'Gathering scholars from different disciplines, this book is the first on how to study emotions using sociological, historical, linguistic, anthropological, psychological, cultural and mixed approaches. Bringing together the emerging lines of inquiry, it lays foundations for an overdue methodological debate.The volume offers entrancing short essays, richly illustrated with examples and anecdotes, that provide basic knowledge about how to pursue emotions in texts, interviews, observations, spoken language, visuals, historical documents and surveys. The contributors are respectful of those being researched and are mindful of the effects of their own feelings on the conclusions. The book thus touches upon the ethics of research in vivid first person accounts. Methods are notoriously difficult to teach--his collection fills the gap between dry methods books and students' need to know more about the actual research practice'--
Machine generated contents note: 1. Introduction: methods of exploring emotions / Helena Flam -- pt. I Emotions -- a legitimate object of study -- 2. Using fiction as sociology: how to analyze emotions with the help of novels / Helmut Kuzmics -- 3. 'It's all in the plot': narrative explorations of work-related emotions / Eda Ulus -- 4. 'Studying up': emotions and finance decisions / Jocelyn Pixley -- 5. Exploring emotion discourse / Tamar Katriel -- 6. The rhetoric of emotions / Barbara Czarniawska -- pt. II Eliciting emotions through interviews -- 7. Researching dark emotions: eliciting stories of envy / Ishan Jalan -- 8. Emotional expertise: emotions and the expert interview / Jochen Kleres -- 9. Dialogic introspection: a method for exploring emotions in everyday life and experimental contexts / Jenny Weggen -- pt. III Observing emotions in self and others -- 10. How do we know what they feel? / Asa Wettergren -- 11. Emotional insights in the field / Stina Bergman Blix -- 12. Emotions: the discovery of an object and the development of a method / Jean Nizet -- 13. Emotional alliances in bureaucratic encounters / Alberto Martin Perez -- 14. Can you feel your research results? How to deal with and gain insights from emotions generated during oral history interviews / Benno Gammerl -- 15. When your data make you cry / Deborah Gould -- 16. Funerary emotions: categorizing data from a fieldwork diary / Julien Bernard -- 17. Researching'emotional geographies' in schools: the value of critical ethnography / Michalinos Zembylas -- pt. IV Speaking emotions -- 18. Indexing anger and aggression: from language ideologies to linguistic affect / H. Julia Eksner -- 19. Emotion and conceptual metaphor / Cristina Soriano -- 20. The intensification and commodification of emotion: declarations of intimacy and bonding in college field trips to the Global South / Gada Mahrouse -- pt. V Emotions in visuals -- 21. Visuals and emotions in social movements / Nicole Doerr -- 22. Evoking emotions: the visual construction of fear and compassion / Francesca Falk -- pt. VI Documented emotions -- 23. 'My heart belongs to daddy': emotion and narration in early modern self-narratives / Claudia Jarzebowski -- 24. How to detect emotions? The cancer taboo and its challenge to a history of emotions / Bettina Hitzer -- 25. The geography and temporality of emotions / Helena Flam -- pt. VII Surveying emotions -- 26. Triangulation as data integration in emotion research / Sylvia Terpe -- 27. Missing values: surveying protest emotions / Dunya Van Troost.
Includes bibliographical references and index.
Keywords: Emotions; Emotions -- Social aspects